2001
DOI: 10.1103/physrevlett.87.205005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Stabilization in theZ-Pinch

Abstract: Theoretical studies have predicted that the Z-pinch can be stabilized with a sufficiently sheared axial flow [U. Shumlak and C. W. Hartman, Phys. Rev. Lett. 75, 3285 (1995)]. A Z-pinch experiment is designed to generate a plasma which contains a large axial flow. Magnetic fluctuations and velocity profiles in the plasma pinch are measured. Experimental results show a stable period which is over 700 times the expected instability growth time in a static Z-pinch. The experimentally measured axial velocity shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 10 publications
2
53
0
Order By: Relevance
“…In higher-S plasmas, Taylor relaxation should be more robust, and other effects outside of standard ideal MHD are surely needed in order to prevent relaxation. We hypothesize that properly driven shear-flows could possibly stabilize the kink, 79,80 as might finite-Larmor radius effects if an energetic neutral beam were injected in the plasma. These hypotheses remain to be tested by experiment and theory.…”
Section: Discussionmentioning
confidence: 99%
“…In higher-S plasmas, Taylor relaxation should be more robust, and other effects outside of standard ideal MHD are surely needed in order to prevent relaxation. We hypothesize that properly driven shear-flows could possibly stabilize the kink, 79,80 as might finite-Larmor radius effects if an energetic neutral beam were injected in the plasma. These hypotheses remain to be tested by experiment and theory.…”
Section: Discussionmentioning
confidence: 99%
“…The ZaP experiment (Shumlak et al, 2001(Shumlak et al, , 2003, shown in Fig. 1, produces a hydrogen Z-pinch column (100 cm long and approximately 1 cm radius) with flow velocities on the order of 100-200 km/s (see Table 1 for more information).…”
Section: The Zap Flow Z-pinch Experimentsmentioning
confidence: 99%
“…A number of magnetic confinement fusion concepts including spheromaks, FRCs, Z-pinches and inertial confinement concepts such as pellet implosion are under investigation at various facilities [1][2][3][4]. An important area of recent numerical research in plasma physics has been the development of plasma simulation algorithms with more complete physics including Hall MHD [5][6][7][8][9][10], and the full two-fluid model [11,12].…”
Section: Introductionmentioning
confidence: 99%